Classical theory of the optical Venn paradox - G. M. Stéphan (AIP Advances)
The optical Venn paradox is observed on light crossing three successive linear polarizers whose axes are oriented along x and y and at 45° between x and y. This observation has not yet been understood within the usual formalism of classical electromagnetism. Here, we develop a classical explanation where the theory is based on the use of potentials.